TINGKAT KEPUASAN SISWA SMAN 8 MALANG TERHADAP MAHASISWA PPG PRAJABATAN SENI BUDAYA UNIVERSITAS NEGERI MALANG - Handi Wiyono; Ahmad Yusuf; Wida Rahayuningtyas; Handi Wiyono; Ahmad Yusuf (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This research aims to measure the level of satisfaction of class The method used is Service Quality. The results of the student satisfaction evaluation show aspects that need to be maintained and improved in the competence of PPG Pre-Service Arts and Culture students. The implications of this research are the need to maintain the quality of pre-service PPG student selection, improve the quality of courses and teaching lecturers that are integrated with PPL activities, provide adequate preparation time for students, as well as the importance of high awareness and motivation from students to increase their competence as prospective teachers. Thus, this research contributes to improving the quality of arts and culture education through evaluating student satisfaction as an indicator of teacher competence.